Pengaruh Ukuran Perusahaan, Arus Kas, Tingkat Utang, Kepemilikan Manajerial Terhadap Persistensi Laba Pada Perusahaan Perbankan Sektor Financial Papan Utama Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2023 - Faisal Arif, Muhammad; Halim, Ardiansyah; Ahmad, Ruslan (Bongaya Journal of Research in Accounting (BJRA), 2025)
This study aims to determine the effect of company size, cash flow, debt level, managerial ownership on profit persistence in banking companies in the main financial sector listed on the Indonesia stock exchange in 2021-2023. This study uses asample of 22 companies. The sampling method used in this study is purposive sampling. The research hypothesis shows that company size has a positive and significant effect on earnings persistence, cash flow is proven to have a significant negative effect on earnings persistence, debt level is proven to have a positive effect on earnings persistence, and managerial ownership is proven to have a significant posistive effect on earnings persistence.